Adjustment of the bioresistivity by electron irradiation: self-assembled monolayers of oligo(ethyleneglycol)-terminated alkanethiols with embedded cleavable group - Krakert, Simone; Ballav, Nirmalya; Zharnikov, Michael; Terfort, Andreas (Physical chemistry, chemical physics, 2010)
The bioresistivity of protein-repelling films, such as e.g. oligoethyleneglycol (OEG) bearing self-assembled monolayers (SAMs), can be adjusted by electron irradiation. We have studied the effect of an embedded irradiation-sensitive functional group (so called “weak link”) on the irradiation sensitivity of such films. As test systems, we used two OEG-substituted alkanethiolate SAMs with different lengths of the OEG chain and a sulfone group serving as a “weak link” moiety; this group was embedded between the OEG and alkyl chains of the target molecules. The expected cleavage of the molecular chains at the predetermined “weak link” position was found to be accompanied by direct damage of the OEG matrix, with a dominance of the latter process in the case of a long OEG chain. At the same time, in the case of short OEG chain, the insertion of sulfone group resulted in a noticeable gain in the irradiation sensitivity of the respective SAMs and, consequently, in enhanced tunability of their protein-adhesive properties. These films, along with other OEG-substituted SAMs and polymer layers with and without an embedded weak link moiety, can be used as primary matrices for the fabrication of different protein patterns by electron beam lithography.
Online veröffentlicht am 16. November 2009
Gesehen am 23.03.2023